Validasi Modul Ajar Berbasis Problem Based Learning pada Materi Sel Kelas XI SMA - Mila Riska Apriana; Heffi Alberida (Al-Alam: Islamic Science Education Journal, 2026)
The Independent Curriculum (Curriculum Merdeka) is a curriculum with diverse intracurricular learning designed to help students understand concepts in depth. This curriculum encourages teachers to develop teaching materials tailored to their students' needs, including teaching modules. Based on the needs analysis, teachers still face challenges in developing teaching modules. This study aims to produce a valid Problem-Based Learning-based teaching module for grade XI high school students on cell material. This research is a research and development study using the Four-D model, limited to three stages: define, design, and develop. The research subjects consisted of three Biology lecturers from the Faculty of Mathematics and Natural Sciences, Padang State University, and three Biology teachers. The results showed a validity value of 92.95%, with a very valid criterion. Thus, the Problem Based Learning-bases teaching module no cell material is suitable for use to support active and meaningful learning in high school.